Organizational performance in BAPAREKRAF Indonesia - Sutan Adil Hendra; Syamsurijal Tan; Tona Aurora Lubis; M. Syurya Hidayat (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
This study aims to analyze the factors that influence the organizational performance of BAPAREKRAF (The Ministry of Tourism and Creative Economic). BAPAREKRAF is the spearhead of a government agency for developing Indonesia's creative economy. This study's respondents are whole civil servants and civil servant candidates in BAPAREKRAF, in 194 respondents. This research shows that transformational leadership, organizational culture, managerial competence, organizational structure, and organizational trust affect organizational performance, but transactional leadership does not affect organizational performance. Besides that, transformational leadership, organizational culture, organizational structure affect organizational trust, but transactional leadership and managerial competence do not affect organizational trust. Furthermore, transformational leadership, transactional leadership, organizational culture, and organizational structure can be mediated by the trust in organizational performance. However, managerial cannot be mediated by trust in BAPAREKRAF's performance in realizing.